Zasady uczciwej konkurencji w przemyśle targowym - Legiędź-Gałuszka, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2009)
The article presents the emergence of the exhibition industry in Poland as an effect of a social and economic transformation, which took place in late 1980s and early 1990s. Several newly established enterprises started to learn the specificity of exhibition industry and to compete with the Poznań International Fair. Lack of professionalism, clear procedures and business reliability often led to misunderstandings and conflicts. Establishing Polish Trade Fair Corporation (PTFC) in 1993 had started the process of setting situation of the industry in order but it did not solve some of the problems. The key problems still regard ethical issues. Although the ethical code of PTFC established rules of just competition, their efficiency depends mostly on their honest abiding. The article presents various examples of breaking the rules and major fields of conflict in the exhibition industry in Poland. In 2007 PTFC was replaced by newly established Polish Chamber of Exhibition Industry (PCEI). Its major challenges are verification of experience of almost twenty years of the exhibition industry in Poland and proposing new version of Ethical Code, so that the representatives of the industry respect it.